Design of a Small NEMP Simulator for the Immunity Test of Core Electronic Components in HEMP Environments - Kim, Young Jin; Jeong, Young Kyung; Youn, Dong Gi; Park, Hyun Ho; Park, Yong Bae (IEEE Access, 2020)
We design a small nuclear electromagnetic pulse (NEMP) simulator to study the immunity of core electronic components in high-altitude electro-magnetic pulse (HEMP) environments. The NEMP simulator comprises of a power device, a high-voltage charging part, a pulse-shaping part, and the input taper. The performance of the proposed simulator is verified by the actual experimental results. The positive and negative polarities for the mono pulse output of a transient pulse generator are checked against the standard. The field uniformity of the proposed NEMP simulator is 1.6 dB and fully meets the standard.
Keywords: Electronic component; Field uniformity; Immunity test; Magnetic pulse; Negative polarity; Nuclear electromagnetic pulse; Power devices; Transient pulse; field uniformity; guided-wave electromagnetic pulse simulator; high-altitude electromagnetic pulse; Nuclear electromagnetic pulse